Idiopathic young-onset Fahr’s disease with schizophrenia-like presentation: a case report - Li, Wen-Cheng; Hsieh, Ya-Chu; Chen, Pei-Ting; Lee, Chia-Ning; Tsai, Tsung-Yu (Frontiers in Psychiatry, 2024)
This case report describes an exceptionally rare case in which a prior diagnosis of schizophrenia was later determined to be early-onset Fahr's disease, linked to a genetic mutation in the SLC20A2 gene. Initially, the patient exhibited symptoms resembling schizophrenia, including aggression and hostility, and was highly susceptible to medication side effects such as restlessness and Parkinsonism. Despite maintaining independent activities of daily living, his neurological examinations revealed hidden weakness on the left side. Following adjustments to the medication regimen, stability was achieved with residual psychotic symptoms under treatment with Risperidone 1.5mg/day, Valproic acid 1500mg/day, and Quetiapine 37.5mg/day. This case underscores the importance of conducting comprehensive imaging studies at the time of initial psychiatric diagnosis, regardless of the apparent typicality of the presentation. Additionally, it emphasizes the need for patience and adherence to the "Start Low and Go Slow" approach in medication management to minimize the risk of exacerbating psychiatric symptoms and aggression.